Früherkennung des Risikos der späteren Implantatlockerung mittels der Röntgen Stereophotogrammetrischen Analyse (RSA) - Seehaus, Frank; Sonntag, R.; Schwarze, M.; Jakubowitz, E.; Sesselmann, S.; Kretzer, J. P.; Hurschler, C. (Orthopäde, 2020)
Background: Aseptic implant loosening is the most common cause of implant revisions in total hip and total knee arthroplasty. Roentgen Stereophotogrammetric Analysis (RSA) represents the current gold standard for the in-vivo assessment of implant fixation. Present situation: Long-term clinical trials have shown that continuous implant migration within the first two postoperative years correlates strongly with a later aseptic loosening. Thus, the implant migration measured with RSA can be regarded as a reliable surrogate marker for later implant loosening. Over the past 40 years, RSA has been continuously further developed, and the model-based RSA approach has reduced the effort involved since markers attached to implant are no longer needed. Perspectives: The RSA method is gaining importance in the certification process of new orthopaedic implants—for example, the Dutch Orthopedic Society has recommended phased-introduction and RSA studies for new hip implants. Furthermore, in the context of the new EU Medical Device Regulation (MDR), which took effect in May 2017, RSA gained relevance for investigating clinically unproven implants. Critics who associate MDR with hindering innovation can be countered in that the RSA method provides a predictive assessment of implant fixation after only two years of follow-up, which is significantly shorter than standard long-term clinical trials.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Implantat fixation; In-vivo-diagnostic; Migration; RSA; Total joint arthroplasty